2022
DOI: 10.1038/s41598-022-15180-z
|View full text |Cite|
|
Sign up to set email alerts
|

Photo-supercapacitors based on nanoscaled ZnO

Abstract: In this study, zinc oxide (ZnO) powders in two different morphologies, nanowire (NW) and nanoflower (NF), have been synthesized by the hydrothermal method. The eligibility of the pristine ZnO nanopowders as a photo-active material has been revealed by designing P-SC devices via the facile drop-casting method on both glass and plastic substrates in large-area applications. The impact of physical properties and especially defect structures on photo-supercapacitor (P-SC) performance have been explored. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…Such defects are reported in nanostructured ZnO with a high specific surface. 43 The second EPR signal with the g -factor at 1.96 was frequently reported in the ZnO structure. Its origin consists of intrinsic defects such as oxygen vacancies and interstitial zinc with the features of shallow donors.…”
Section: Resultsmentioning
confidence: 85%
“…Such defects are reported in nanostructured ZnO with a high specific surface. 43 The second EPR signal with the g -factor at 1.96 was frequently reported in the ZnO structure. Its origin consists of intrinsic defects such as oxygen vacancies and interstitial zinc with the features of shallow donors.…”
Section: Resultsmentioning
confidence: 85%
“…All diffraction peaks are well indexed with the hexagonal phase of ZnO wurtzite crystal structure with (100), (002), (101), (102), (110), (103), (112), and small (201) and (202) crystal planes (JCPDS 36–1451). 20 , 45 On the other hand, the intensities of the peaks vary with the annealing temperature for all morphologies, 53 which is most probably owing to the improvement in crystallinity of the samples as smaller grains inosculate to form larger ones, leading to an increase in average crystallite size as the temperature increases. 37 , 54 The crystallite size has been estimated using Scherrer’s equation for all samples, and the largest crystallite size has been observed at 800 °C with 50.97, 50.94, and 44.40 nm for NF, NS, and NU, respectively ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided reports on the alternative development of supercapacitor energy storage devices using biowastes. They concluded that carbon-based materials are supercapacitor electrode material that offers high specific surface area, good conductivity, and excellent stability in harsh environments and that supercapacitor electrode material from biowaste helps in converting waste into a useful product and improve the supercapacitor technology [32] .…”
Section: Pseudo-capacitor Hybrid Capacitormentioning
confidence: 99%